Identification of Potential Biomarkers from Aconitum carmichaelii, a Traditional Chinese Medicine, Using a Metabolomic Approach - Zhao, Dake; Shi, Yana; Zhu, Xinyan; Liu, Li; Ji, Pengzhang; Long, Chunlin; Shen, Yong; Kennelly, Edward J. (Planta Medica, 2018)
Despite their well-known toxicity, Aconitum species are important traditional medicines worldwide. Aconitum carmichaelii, known in Chinese as 附子 (fuzi), is an officially recognized traditional Chinese medicine with characteristic analgesic and anti-inflammatory activities, whose principal pharmacological ingredients are considered as aconitine-type diterpene alkaloids. Notwithstanding the long-recorded use of A. carmichaelii in traditional Chinese medicine, no single-entity aconitum alkaloid drug has been developed for clinical use. UPLC-Q-TOF-MS was used to investigate the marker compounds that can be used to differentiate A. carmichaelii from seven other Aconitum species collected in Yunnan Province. Nontargeted principle component analysis scores plots found that all the tested Aconitum species clustered into three distinct groups, and A. carmichaelii was significantly different chemically than the other seven species. Furthermore, the primary and lateral roots of A. carmichaelii also showed significant differences. Using orthogonal partial least squares discriminate analysis analysis, eight marker compounds were identified, including 14-acetylkarakoline, aconitine, carmichaeline, fuziline, hypaconitine, mesaconitine, neoline, and talatisamine. Four of these aconitum alkaloids, fuziline, hypaconitine, mesaconitine, and neoline, showed significant analgesic activity in a dose-dependent manner compared to the negative and positive controls. However, hypaconitine, mesaconitine, and neoline exhibited significant acute toxicity activity, while fuziline showed no acute toxicity in mice, suggesting the relative safety of this alkaloid. This study provides a good example of how to differentiate an authentic medicinal plant from common adulterants using a metabolomics approach, and to identify compounds that may be developed into new drugs.
Keywords: Aconitum; Aconitum carmichaelii; Ranunculaceae; aconitum alkaloids; diterpene alkaloids; analgesic activity; acute toxicity; traditional Chinese medicine; TCM